2015
DOI: 10.1007/s12262-015-1286-8
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in the Management of Congenital Diaphragmatic Hernia in Infants

Abstract: The therapeutic approach to congenital diaphragmatic hernia (CDH) has shifted from one of immediate repair to management of pulmonary hypertension, physiologic stabilization, and delayed surgical repair. Lung hypoplasia, remodeled pulmonary vasculature, and ventricular dysfunction all contribute to the high morbidity and mortality associated with CDH. In addition, genetic syndromes associated with CDH can increase the incidence of serious anomalies and hence impact survival. Prenatal and postnatal management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…Some authors have defined these criteria as stable mean blood pressure for gestational age, preductal oxygen saturation in the range of 85%–95% on ≤50% oxygen, urine output >2 cc/kg/h, and serum lactate levels <3 mmol/l. 24 Pulmonary artery pressure also determines stability. Some surgeons operate only if normal measures are maintained for at least 24 to 48 h based on echocardiography because they believe that pulmonary hypertension is a major risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have defined these criteria as stable mean blood pressure for gestational age, preductal oxygen saturation in the range of 85%–95% on ≤50% oxygen, urine output >2 cc/kg/h, and serum lactate levels <3 mmol/l. 24 Pulmonary artery pressure also determines stability. Some surgeons operate only if normal measures are maintained for at least 24 to 48 h based on echocardiography because they believe that pulmonary hypertension is a major risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Lung hypoplasia is the major determinant of survival, and the degree of pulmonary hypoplasia correlates with the severity of PPHN. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…The presence of liver herniation into the chest (liver up) is considered to be a poor prognostic indicator. [ 8 9 10 15 ] Some studies have reported higher mortality among the right-sided CDH[ 12 13 14 15 16 17 ] whereas others did not find a statistical difference in mortality rate when compared to left-sided defects. [ 15 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…Deep sedation and neuromuscular blockade were provided selectively in the event of higher ventilation or oxygen requirements. [ 6 7 ] The aim was to achieve preductal SaO 2 of 80%–95%, postductal SaO 2 > 70%, arterial pCO 2 between 45 and 60 mm Hg, and a pH of 7.25–7.40. [ 7 8 9 10 ] Oxygen supplementation was titrated to achieve a preductal saturation of 85%–95%.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…[ 6 7 ] The aim was to achieve preductal SaO 2 of 80%–95%, postductal SaO 2 > 70%, arterial pCO 2 between 45 and 60 mm Hg, and a pH of 7.25–7.40. [ 7 8 9 10 ] Oxygen supplementation was titrated to achieve a preductal saturation of 85%–95%. The preferred ventilation strategy was pressure-cycled ventilator with initial continuous mandatory ventilation, followed by intermittent mandatory ventilation, peak inspiratory pressure (PIP) <25 cm H 2 O, positive end-expiratory pressure (PEEP) of 3–5 cm H 2 O, and ventilator rate of 40–60/min.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%